2020
DOI: 10.31234/osf.io/kr578
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Health warning labels and alcohol selection: a randomised controlled experiment in a naturalistic shopping laboratory

Abstract: Background and aims Health warning labels (HWLs) on tobacco products reduce smoking. There is an absence of evidence concerning the impact of alcohol HWLs on selection or purchasing in naturalistic settings. Using a commercial-standard naturalistic shopping laboratory, this study aimed to estimate the impact on selection of alcoholic drinks of HWLs describing adverse health consequences of excessive alcohol consumption.DesignA between-subjects randomised experiment with three groups: Group 1: image-and-text HW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…In total, we identified 27 papers that fit our inclusion criteria (see Appendix A for PRISMA diagram) [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. One paper reported on two studies using different methodologies to study the same variables [ 50 ], and four papers reported on different aspects of one intervention [ 51 , 52 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In total, we identified 27 papers that fit our inclusion criteria (see Appendix A for PRISMA diagram) [ 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. One paper reported on two studies using different methodologies to study the same variables [ 50 ], and four papers reported on different aspects of one intervention [ 51 , 52 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…One paper reported on two studies using different methodologies to study the same variables [ 50 ], and four papers reported on different aspects of one intervention [ 51 , 52 , 53 , 54 ]. The remaining papers were individual studies (with a complete or partial focus on alcohol HWL labelling), although some of them were part of the same research line of label development and testing (e.g., [ 55 , 56 , 57 , 58 , 59 , 60 ]) or studied the same labels (e.g., [ 61 , 62 ]).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations